High efficacy and students’ satisfaction after voluntary vs mandatory use of an e-learning program in traumatology and orthopedics: a follow-up study - Back, David Alexander; Haberstroh, Nicole; Sostmann, Kai; Schmidmaier, Gerhard; Putzier, Michael; Perka, Carsten; Hoff, Eike (Journal of surgical education, 2014)
Introduction - Within the last decade, e-learning has gained a consistent place in surgical teaching. However, as the use of new programs is often voluntary, more information on the implications of the data regarding user acceptance and knowledge with mandatory use is desirable, especially in the context of the long-term developments of courses. - Materials - Starting in 2009, the e-learning program Network for Students in Traumatology and Orthopedics was offered in a voluntary blended learning context. Students’ satisfaction and increase in knowledge were evaluated using questionnaires and written tests. With proven effectiveness, the program became a mandatory part of the curriculum, and students’ attitudes and gain of knowledge were re-evaluated in 2010 and 2011 to detect differences in voluntary vs mandatory use. - Results - In the evaluation questionnaires (n = 108 voluntary vs n = 361 mandatory), the overall appreciation regarding the offerings remained high. Significantly more students felt better prepared for clinical situations (p < 0.001) and asked for e-tutoring (p = 0.025) with mandatory use. In written tests, both voluntary (n = 70) and mandatory (n = 147) users showed significantly increased knowledge (p < 0.001). Starting with a lower base level (p < 0.001), mandatory users had a significantly higher absolute increase compared with voluntary users (p = 0.015), leading to a similar final level. - Discussion - The presented blended learning concept was an efficient way to teach students orthopedics and traumatology. Data can support the assumption that even if the voluntary evaluation of e-learning offerings might be subject to a selection bias, the results can serve as a representative impression for the students’ overall mood and their gain in knowledge. However, as changes would have to be anticipated when shifting to mandatory use, users’ perceptions should be constantly evaluated.
Gesehen am 02.09.2020